Impact of Seaweed Liquid Extract Biostimulant on Growth, Yield, and Chemical Composition of Cucumber (Cucumis sativus) - Shimaa M. Hassan; Mohamed Ashour; Nobumitsu Sakai; Lixin Zhang; Hesham A. Hassanien; Ahmed Gaber; Gamal Ammar (Agriculture, 2021)
Seaweed extract biostimulants are among the best modern sustainable biological plant growth promoters. They have been proven to eliminate plant diseases and abiotic stresses, leading to maximizing yields. Additionally, they have been listed as environmentally friendly biofertilizers. The focus of the present research is the use of a commercial seaweed biostimulant as an eco-friendly product (formally named True Algae Max (TAM). During the 2017 and 2018 seasons, five treatments of various NPK:TAM ratios were applied via regular fertigation, namely a conventional treatment of 100% NPK (C0) alongside combinations of 25%, 50%, 75%, and 100% (C25, C50, C75, and C100) of TAM, to evaluate the effectiveness of its bioactive compounds on enhancing growth, yield, and NPK content of cucumber (Cucumis sativus) under greenhouse conditions. TAM is rich in phytochemical compounds, such as milbemycin oxime, rhodopin, nonadecane, and 5-silaspiro [4.4]nona-1,3,6,8-tetraene,3,8-bis(diethylboryl)-2,7-diethyl-1,4,6,9-tetraphenyl-. Promising measured parameter outcomes showed the potentiality of applying TAM with and without mixes of ordinary NPK application. TAM could increase cucumber yield due to improving chemical and physical features related to immunity, productivity, and stress defense. In conclusion, it is better to avoid applying mineral fertilizers, considering also that the organic agricultural and welfare sectors could shortly depend on such biotechnological tools and use them to fulfill global food demands for improved sustainability.